Optimalisasi Ekonomi Kreatif Hilirisasi Hasil Hutan Bukan Kayu (HHBK) Mangrove di Desa Kayu Ara Permai Kecamatan Sungai Apit Kabupaten Siak - Mashur, Dadang; Rusli, Zaili; Sadad, Abdul; Zulkarnaini, Zulkarnaini; Nasution, Mimin Sundari; Ananda, Fajriani (Unri Conference Series: Community Engagement, 2024)
The Laskar Mandiri Kampung Kayu Ara Permai Conservation Group uses the mangrove forest to become an edutourism-based tourist attraction with the name Mangrove Sungai Bersejarah (MSB) Edutourism. The problem with managing mangrove tourism is that on average it only relies on the natural charm of mangroves, so visitors are reluctant to visit again. Likewise what happens in MSB tourism, the use of non-timber forest products (NTFPs) from mangroves can be a special attraction in the mangrove area and can also improve the group's economy. The absence of a tourist attraction is the basis for the downstream dedication of mangrove NTFPs as a creative economic group so that it can provide added value to tourist areas. The method used is to provide knowledge and training to groups about the importance of developing NTFPs in tourist areas. The findings show that there is potential for NTFPs that can be developed, such as mangrove batik, dodol, mangrove coffee, kedabu syrup, jeruju sticks, kedabu jam, waru peyek and bolu berembang. The conclusion of the service is that MSB tourism can be developed not only in the edutourism aspect, but can also be developed in the minatourism aspect through NTFPs.